2014
DOI: 10.1504/ijvnv.2014.059627
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and bio-dynamic model development of seated human subjects exposed to low frequency vibration environment

Abstract: In this study, the effect of posture, vibration magnitude and frequency on seat-to-head (STH) and back support-tohead (BTH) transfer functions has been studied under vertical sinusoidal vibration. Twelve healthy male subjects were participated in experimental work to measure vertical vibration transmitted to the occupants head in three representative postures (erect, vertical back on and forward lean on table) under three magnitudes of vibration (0.4, 0.8 and 1.2 m/s 2 r.m.s.) in frequency range 1 to 20 Hz. Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 18 publications
2
24
0
Order By: Relevance
“…Results obtained clearly establish decoupling of vertical and fore-and-aft oscillations. The results have been compared with the values available in the literature and it was found that the eigenvalues evaluated in the present work are comparable with the resonant frequency peaks obtained from the experimental data given by Harsha et al (2014), Gupta (2007), Griffin (1997, 1998) and Rutzel, Hinz, and Wolfel (2006).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Results obtained clearly establish decoupling of vertical and fore-and-aft oscillations. The results have been compared with the values available in the literature and it was found that the eigenvalues evaluated in the present work are comparable with the resonant frequency peaks obtained from the experimental data given by Harsha et al (2014), Gupta (2007), Griffin (1997, 1998) and Rutzel, Hinz, and Wolfel (2006).…”
Section: Discussionsupporting
confidence: 80%
“…The present study deals with a nine-DOF lumped parameter model developed by Harsha et al (2014) in order to study the response of seated human body to the vertical and horizontal whole-body vibrations, considering five segments of masses interconnected by four vertical and two horizontal springs and dampers such that seat and feet are fixed with respect to floor with the help of two vertical and two horizontal springs and dampers with hands resting on the lap. This model has been modified in the present study for which anthropometric data of Indian male subjects have been taken from Chakrabarti (1997).…”
Section: Description Of Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The magnitudes also varied considerably from the standardized values . It can be seen from Figure that the STHT values of the model were within the variations available in the literature …”
Section: Validation Of the Modelsupporting
confidence: 73%